The Nep1-like protein family of Magnaporthe oryzae is dispensable for the infection of rice plants - Ya-Li Fang (Nature Portfolio, 2017)
Abstract The necrosis- and ethylene-inducing protein 1 (Nep1)-like proteins (NLPs) are a class of microbe-associated molecular patterns widely distributed across diverse groups of plant-associated microorganisms. In spite of the cytotoxic activity in dicot plants, the role of most NLPs in the virulence of plant pathogens is still largely unknown. We showed that the MoNLP family of rice blast fungus varied very little in amino acid sequence, transient expression of three MoNLPs induced cell death and the production of reactive oxygen species in Nicotiana benthamiana, and the expression of MoNLPs was induced during infection of susceptible rice plants. To further investigate the biological role of the MoNLP family, a marker-free gene replacement vector was developed and used to knock out the whole family in Magnaporthe oryzae. Results showed no significant difference in disease levels caused by wild type and the quadruple ΔMoNLP mutant strains. Likewise, the sporulation and radial growth of the two strains were similar under various unfavorable cultural conditions including malnutrition and abiotic stresses. These observations demonstrated that the MoNLP family is dispensable for the fungal tolerance to the tested adverse cultural conditions, and more importantly, for the virulence of blast fungus on susceptible rice plants.